FREQUENCY OF DEPRESSION AMONG FERTILE AND INFERTILE WOMEN: Depression Among Fertile and Infertile Women - Qayyum, Mamuna; Ahmed, Shoaib; Kanwal, Shamsa; Ishfaq, Yusra; Hassan, Haleema; Ali, Waleed; Waheed, Nomira; Shoaib, Kiran (Pakistan Armed Forces Medical Journal, 2014)
Objective: To compare the frequency of depression among fertile and infertile women reporting in CMH Abbottabad.Study Design: A case control study.Place and Duration of Study: This study was conducted in Combined Military Hospital Abbottabad, over a period of six months from January 2013 to June 2013.Patients and Methods: The inclusion criteria were all those patients who were married. All the cases were selected from the women reporting in the obstetrics and gynecology department of CMH Abbottabad for investigation and treatment of infertility. A total of 200 patients, 100 fertile and 100 infertile women were included. Patients were given questionnaire form with their consent for research. Beck depression inventory (BDI) was used to assess depression among fertile and infertile women. Other factors such as age, educational level, and duration of infertility, pressure from family members, miscarriages, and support from husband were studied.Results: Depression was significantly higher in infertile women as compared to fertile women i.e. 95% vs. 63% (p < 0.001). It was higher among women with more than 1 year of duration of marriage as compared to those with infertility of one year duration or less.Conclusion: Infertility is associated with depression.